Influence of population size, density, and proximity to talent clubs on the likelihood of becoming elite youth athlete - Rossing, N. N.; Stentoft, D.; Flattum, A.; Côté, J.; Karbing, D. S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Previous studies have found significant differences in the likelihood of becoming an elite athlete depending on community population sizes and densities, an effect known as the place of early development, or birthplace effect. However, the results have not been consistent between sports or European countries. As both professional and voluntary clubs are vital to the talent development systems in Europe, the proximity of an athlete's place of early development to the location of talent clubs may be an important predictor of the likelihood of becoming an elite athlete. Therefore, the primary purpose of this study was to investigate the place of early development effect and the effect of proximity to talent clubs. The samples included elite youth league athletes (579 football and 311 handball) and national youth athletes (85 football and 80 handball) and a comparison group of 147 221 football and 26 290 handball youth athletes. Odds ratios showed variations in the optimal community size and density across sports. Geospatial analyses of proximity to talent clubs highlighted a trend indicating that most national and elite youth league athletes in both sports had their place of early development in their sport near a talent club. The results suggest that proximity is an important predictor in the development of expertise across sports, but future studies need to clarify if proximity is important in other countries and sports.